Chapter 1 Through a net darkly Spatial expression from glossematics to schizoanalysis - Doel, Marcus A. (Taylor & Francis, 2019)
The chapter works through a constellation of fractured and fissured geo-graphical terms that give spatial expression to what Félix Guattari and Gilles Deleuze famously called 'schizoanalysis' and 'geo-philosophy'. This constellation takes flight from a semiotic impasse bequeathed to us by the combined forces of structuralism and poststructuralism (especially in the work of Ferdinand de Saussure, Jacques Lacan, and Jacques Derrida), which left in its wake nothing but broken, splintered, and malfunctioning signs stretching out before us in all directions. However, while shattered and enigmatic signs may prove all the more captivating and seductive, especially for a 'society of the spectacle', the insatiable desire that their fractal enchainment unleashes should not be mistaken for revolutionary desire. To put it bluntly, the militant injunction Revolt! is indistinguishable from the reactionary injunction Enjoy!. Once enthralled by its alluring chains, there is no escaping the signifier. All the exits are blocked. Through a forced reading of Louis Hjelmslev, however, Guattari discovered a way out of the swamp of signs. Following in Guattari's wake, the chapter argues that a world shatters not by virtue of the weight of great numbers, but by virtue of the ineradicable hairline cracks that run through the middle of things.